2021
DOI: 10.1037/apl0000865
|View full text |Cite
|
Sign up to set email alerts
|

When there is a will there is a way: The role of proactive personality in combating COVID-19.

Abstract: The global COVID-19 pandemic has disrupted personal and work lives and created great uncertainty and stress, especially for frontline health care professionals like doctors and nurses who risk personal health while facing increased workloads and new COVID-related tasks. People can passively respond to this disruption, or they can be more active and choose to shape the conditions surrounding their work during the crisis. We designed a multiwave, multisource study examining whether a proactive orientation is a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 74 publications
3
48
0
2
Order By: Relevance
“…Third, while core self‐evaluations and future focus are important personality traits, other traits are potentially also important in terms of how support affects job‐related well‐being. Research has, for instance, found that the interplay between perceived organizational support and proactive personality matters for individual outcomes during the pandemic (Yi‐Feng Chen et al, 2021 ). Future research could explore additional personality traits that are likely to affect how employees experience organizational and managerial support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, while core self‐evaluations and future focus are important personality traits, other traits are potentially also important in terms of how support affects job‐related well‐being. Research has, for instance, found that the interplay between perceived organizational support and proactive personality matters for individual outcomes during the pandemic (Yi‐Feng Chen et al, 2021 ). Future research could explore additional personality traits that are likely to affect how employees experience organizational and managerial support.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lee and Jeung ( 2018 ) find that perceived organizational support is more important in stimulating affective commitment to the organization for employees with a low status than for those with a high status in the organization. Yi‐Feng Chen et al ( 2021 ) also highlight the importance of considering personality traits as they find in a sample of front line health care professionals working during the COVID‐19 pandemic that proactive personality interacts with perceived organizational support to influence well‐being outcomes (i.e., thriving).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…A proactive personality secures the psychological resources under stressful COVID-19 conditions (Yi-Feng Chen et al, 2021). Proactive personality is a process by which individual influences the environment (Bateman and Crant, 1993).…”
Section: Moderating Role Of Leader Proactive Personalitymentioning
confidence: 99%
“…Taking together, the proactive personalities of leader and follower enhance job satisfaction (Zhang et al, 2012). Proactive personality is positively related to motivational resources even in COVID-19 crises (Yi-Feng Chen et al, 2021). Prior studies have recommended that a leader's proactive personality can be a boundary condition (Chiu et al, 2016;Wang and Liang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study by Zacher and Rudolph (2021) collected data from 979 individuals in Germany and found that individual differences in life satisfaction, positive affect, and negative affect result in different types and levels of coping strategies during the COVID-19 crisis (e.g., controllability appraisals, positive reframing, using emotional support, self-blame). Furthermore, utilizing a sample of 408 doctors and nurses in Wuhan City, China, another study by Yi-Feng Chen et al (2021) found that proactive personality tends to influence one's performance, resilience, and thriving through strengths use during the COVID-19 crisis. Such findings from multiple countries emphasize the importance of individual differences and its persistence in coping with the COVID-19 crisis.…”
Section: Theoretical Implicationsmentioning
confidence: 99%